Market as Engine of Historical Change: A Comparative Historical Analysis of Sociology of Market - Radhika Devi Dahal, (Interdisciplinary Journal of Management and Social Sciences, 2023)
Market is social phenomenon. This article argues that market is social phenomenon because, people perform according to their social positioning. Historically, market was changing, as per the social change. There are different stages of the market development, it was started from kinship to capitalist market.